If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2(1/2(7x-6)=6x-10)
We move all terms to the left:
2(1/2(7x-6)-(6x-10))=0
Domain of the equation: 2(7x-6)-(6x-10))!=0We multiply all the terms by the denominator
x∈R
2(1=0
We add all the numbers together, and all the variables
=0
x=0/1
x=0
| -5a+7a=-28+3a+5a | | 8=3/4a+18-a+4 | | m/16=-1/2 | | 29.95+0.16(270)=m | | M+7-5m=23 | | 8000+8000(.20-x=7200 | | 4x+2=81+13x-7 | | 11/12=3-4h | | 7=7-8x+8 | | 3/4x+3-2x=-1/4 | | 4.8+9=2.8g+19 | | 10.95x+12-57=89.22 | | -8b-3b=-22 | | 4.2(s-15.3)+6.96=17.04 | | 5.5g+10=3.5+22 | | 2.9x-17.8=-9.1 | | *3+5a=4a-10 | | (8x+9)(4x-9)=0 | | 5=3/7b | | 4n=3n-1 | | 5.5g+9=3.5+22 | | 13x+20=-16+16x | | 5x-157+7x=47 | | 9x-8=-42 | | -21=6m-8+7m | | -12+11x+2x=11x+10 | | -23-8x+5x=57 | | 3=5m-5-m | | 4a=8.5 | | -125+x-8x=78 | | 4.9x-3.5=25.9 | | -6x-21=-9x+2x |